2014
DOI: 10.1002/smll.201400017
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk‐Derived Graphene with Nano‐Sized Domains and Clean Edges

Abstract: A new synthetic method is demonstrated for transforming rice husks into bulk amounts of graphene through its calcination and chemical activation. The bulk sample consists of crystalline nano-sized graphene and corrugated individual graphene sheets; the material generally contains one, two, or a few layers, and corrugated graphene domains are typically observed in monolayers containing topological defects within the hexagonal lattice and edges. Both types of graphenes exhibit atomically smooth surfaces and edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(129 citation statements)
references
References 34 publications
6
121
0
2
Order By: Relevance
“…In addition, the intensified and narrower G band can be further considered as an ordering of amorphous carbon (Muramatsu et al, 2014). As such, if the D3 band is determined as amorphous carbon, then logically, the intensity of D3 should be weakened as well.…”
Section: Raman Result D Band and G Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the intensified and narrower G band can be further considered as an ordering of amorphous carbon (Muramatsu et al, 2014). As such, if the D3 band is determined as amorphous carbon, then logically, the intensity of D3 should be weakened as well.…”
Section: Raman Result D Band and G Bandmentioning
confidence: 99%
“…However, CVD approaches tend to be unreliable when scaled up, since the process requires a thin metallic substrate. Moreover, epitaxial growth requires an expensive silicon carbide (Muramatsu et al, 2014). The production of graphene-like material from coconut coir dust has been done, but it requires high temperatures of up to 1500 o C (Barin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Principal examples of these methods subsume mechanical and electrochemical exfoliation of graphite [1], reduction of graphene oxide [2], chemical vapor deposition [3], and thermal decomposition of SiC [4]. In addition, a new form of domain-based graphene is available from rice husks, via a fusion process with potassium hydroxide at 1123 K [5].…”
Section: Introductionmentioning
confidence: 99%
“…Principal examples of these methods subsume mechanical and electrochemical exfoliation of graphite [1], reduction of graphene oxide [2], chemical vapor deposition [3], and thermal decomposition of SiC [4]. In addition, a new form of domain-based graphene is available from rice husks, via a fusion process with potassium hydroxide at 1123 K [5].Of particular interest is developing a rapid, one-pot procedure that is also potentially scalable, high-yield and devoid of the use of toxic reagents. Our lamp ablation method for the synthesis of few-layer graphene ( Fig.…”
mentioning
confidence: 99%
“…This assumption was not unreasonable because AB stacking (interplanar spacing 3.35 Å) is the minimum energy configuration for planar graphene layers and the less stable AA stacking (interplanar spacing 3.53 Å) is not present in pure crystalline graphite2. With the progress in fabricating mono- and multilayer graphene3, unique Moiré patterns45678 are revealed arising from the atomic-resolution transmission electron microscopy (TEM) morphology with rotating angles between graphene planes (i.e., disorderly stacked), and are proved as the signature of disordered graphite. Recently, we have shown that AA’ stacking of graphene planes (where each graphene plane is shifted by 1/2 hexagon from zigzag AA stacking or by 1/4 hexagon from armchair AB stacking) exists, and may be the structure of multi-wall carbon nanotubes (MWNTs) (i.e., helically grown AA’ graphite)910.…”
mentioning
confidence: 99%